2021
DOI: 10.1007/s12325-021-01890-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Compassionate Drug Use During the First Wave of the COVID-19 Pandemic: A Retrospective Single-Center Study

Abstract: Introduction Concomitant experimental/compassionate drug administration has been all-pervasive in the treatment of COVID-19 patients. The objective of this study was to study the relationship between patient severity, the number of experimental/compassionate medications received (main outcome measure), and patient outcomes [survival to hospital discharge and length of hospital stay (LOS)]. Methods Retrospective analysis of data collected in real time during the first pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The lack of treatment effect in this subpopulation may be explained by the greater severity of the underlying COVID-19 lung disease reflected by the higher inspired oxygen requirements, lower lymphocyte counts and elevated inflammatory markers at baseline, which may, in turn suggest that there may be a threshold level for disease irreversibility. 20 Cox regression analysis demonstrated that mortality outcome differences in the FiO 2 <60% subpopulation between opaganib and placebo were independent of potential baseline characteristics confounders: in addition, the differences in severity between the 06/08/22 low FiO 2 (≤60%) and high FiO 2 (>60%) subpopulations were independent of disease duration.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The lack of treatment effect in this subpopulation may be explained by the greater severity of the underlying COVID-19 lung disease reflected by the higher inspired oxygen requirements, lower lymphocyte counts and elevated inflammatory markers at baseline, which may, in turn suggest that there may be a threshold level for disease irreversibility. 20 Cox regression analysis demonstrated that mortality outcome differences in the FiO 2 <60% subpopulation between opaganib and placebo were independent of potential baseline characteristics confounders: in addition, the differences in severity between the 06/08/22 low FiO 2 (≤60%) and high FiO 2 (>60%) subpopulations were independent of disease duration.…”
Section: Discussionmentioning
confidence: 92%
“…The lack of treatment effect in this subpopulation may be explained by the greater severity of the underlying COVID-19 lung disease reflected by the higher inspired oxygen requirements, lower lymphocyte counts and elevated inflammatory markers at baseline, which may, in turn suggest that there may be a threshold level for disease irreversibility. 20…”
Section: Discussionmentioning
confidence: 99%
“…The use of hydroxychloroquine in intensive care unit (ICU) patients is an example of wasted resources, where these critically ill COVID-19 patients could have been included in other trials. In an interesting study regarding experimental and compassionate drug use during the first wave of the COVID-19 pandemic [ 69 ], the authors highlighted that this kind of treatment was unrelated to survival. A good conceptual model of the time-course of COVID-19 infection from the asymptomatic phase to more severe phases in patients who develop critical illness was proposed by Angriman et al [ 70 ].…”
Section: Immunomodulatory Treatment Of Moderate-to-severe Covid-19—di...mentioning
confidence: 99%
“…That practice, without clear disclosure of duplicate reporting, may affect subsequent estimates and preclude valid meta-analyses. The authors of an interesting retrospective, single-center study regarding experimental and compassionate drug use during the first wave of the COVID-19 pandemic [ 69 ] demonstrated that the administration of multiple experimental/compassionate medications to the same patient not only does not improve survival rates but the true effect of any single drug remains questionable even after adjusting for the receipt of additional treatments. In these circumstances, it is more difficult to identify a potential cure.…”
Section: Covid-19 Pandemic Brought Basic and Therapy Trials Into The ...mentioning
confidence: 99%